Effects of a quenching treatment on PCDD/F reduction in the bottom ash of a lab waste incinerator to save the energy and cost incurred from post-thermal treatment. (15th July 2019) - Lin, Sheng-Lun; Lee, Kuan-Lin; Wu, Jhong-Lin; Kiprotich Cheruiyot, Nicholas
Highlights: Heterogeneously reaction and condensation increased the PCDD/Fs in bottom ash. Quenching treatment reduced PCDD/F to 1/300 in bottom ash of an incinerator. PCDD/Fs in bottom ash were dominated by highly-chlorinated congeners. Quenching for bottom ash greatly saved energy and CO2e from plasma treatment. It will be 351 tons CO2e/year reduced from plasma system for bottom ash treatment. Abstract: Bottom ash (BA) from incineration has been reused as a construction material for years. However, thermal treatments, which incur extra cost and higher energy demand, are essential to reduce/stabilize the polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) in BA, which can be released from BA during the next startup and cause peak emissions. In this study, the bottom ash from a laboratory waste incinerator (LWI) was collected and quenched at various temperatures during three shutdown operations to determine the results of the gradual cooling process. The PCDD/F content in the BA was quantified using gas chromatography-mass spectrometry. The PCDD/Fs in BA was significantly lower (0.0239 ng WHO-TEQ g −1 ) after being quenched at >400 °C, which was only 1/300 of that in the sample gradually cooled to <200 °C (6.21 ng WHO-TEQ g −1 ). The PCDD/PCDF ratios were less than 1 in all of the samples, suggesting that de novo synthesis might be the predominant formation mechanism, and exponential relationships between the PCDD/F growth ratio and quenching temperature were found, with an r 2 > 0.97. In other words, careful operation of the cooling process is an important PCDD/F inhibition strategy and effectively reduces the subsequent startup emissions. Interestingly, the extremely low PCDD/F levels in the BA after quenching were found to further save the cost of thermal treatment, reduce electricity use by 500 MWh, and lower fuel consumption by 27 kL of diesel, as well as reducing annual CO2e emissions by 351 tons in an LWI. This finding could be further applied to simultaneously control PCDD/F emissions, save post-treatment costs, and reduce the secondary pollutants in other incinerators.